Diagnostic Accuracy of Ultrasound for Malignant Ovarian Cancer Taking Histopathology as Gold Standard - Amina Hameed, Lala Rukh, Khadija Ashraf, Irshad Ahmad, Jahangir, Jamshed Khan, (Pakistan Journal of Medical & Health Sciences, 2023)
Background: Ovarian cancer is the fifth most common and the most aggressive gynaecological malignancy. Ultrasound is the initial and important imaging method for ovarian cancer detection and is an accurate technique for diagnosis and follow up of ovarian cancers. Objective: To find out the diagnostic accuracy of ultrasound for malignant ovarian cancer taking histopathology as gold standard Study Design: Cross Sectional Study Place and Duration: Department of Diagnostic Radiology and Intervention, Sir Ganga Ram Hospital, Lahore in collaboration with the Department of Gynecology and Obstetrics during from the period 11th Jan, 2019 to 11 th July, 2019. Materials and Methods: All referred patients fulfilling the selection criteria was included in the study. After obtaining informed consent, the patients were undergone ultrasound using convex probe of 3.5 MHz frequency using Toshiba NEMIO XG ultrasound machine. Few days after ultrasound, each patient had ultrasound guided biopsy of the lesions in department of Diagnostic Radiology and histopathological data was collected. The above mentioned information was recorded on the patient proforma. Results: Total 225 patients were included according to the inclusion criteria of the study. Mean age (years) in the study was 35.33+6.36 average BMI of the patients was 21.15+2.35. The sensitivity, specificity, PPV, NPV and diagnostic accuracy of ultrasound for malignant ovarian cancer taking histopathology as gold standard was 76.56%, 14.43%, 54.14%, 31.82% and 49.78% respectively. Conclusion: The study concluded that the sensitivity of ultrasound for malignant ovarian cancer taking histopathology as gold standard is substantial. Hence supporting the effectiveness of conventional abdominal ultrasound which can diagnose malignant ovarian cancers and characterization of ovarian masses. Keywords: Ovarian Cancer, Diagnostic Accuracy, Ultrasound